Anthropometric profile of elite women's volleyball players in the Philippines - Christian Wisdom Magtajas Valleser; Katherine Adrielle R. Bersola; Marla Frances T. Mallari; Emmanuel Liberato V. Papa; Francis Carlos B. Diaz; Mona Liza A. Maghanoy; Catherine Joy D. Lariosa (Turkish Journal of Kinesiology, 2018)
The purpose of this study is to determine the anthropometric profile of elite women's volleyball players in the Philippines. Thirty-six (n=36) subjects with a mean age of 23.9 + 3 years participated in this study and were measured by ISAK-certified anthropometrics. Results showed that elite Filipino women's volleyball players are relatively taller and heavier than average Filipino females but smaller and lighter than most internationally-successful women's volleyball teams. They are in the athletic body fat percentage range with a somatotype of endomorph-mesomorph on average. Middle blockers are tall, thin and lean with a mean central somatotype with lengthy extremities. Outside hitters and opposite spikers are relatively tall, lengthy, and muscular with a mean endomorph-mesomorph somatotype. Liberos are shorter and lighter overall with low body fat and a generally endomorphic mesomorph somatotype. Setters are relatively shorter, heavier and larger with higher body fat and an endomorph-mesomorph somatotype on average. Various similarities and differences with related studies are also discussed.